Аналітична теорія плазмонних ефектів у стрижнеподібних металевих наночастинках. Модель еквівалентного сфероїда - Korotun, A.V.; Karandas, Ya.V.; Reva, V.I. (Publishing house "Academperiodika", 2023)
In the framework of the model of equivalent prolate spheroid, analytical expressions for the polarizabilities of rod-like metal structures have been derived, which substantially simplified the calculation of their optical characteristics. The frequency dependences of the transverse and longitudinal components of the polarizability tensor, as well as the absorption and scattering cross-sections, are calculated for prolate spheroids, cylinders, and spherocylinders. The changes in the positions of the maxima of the imaginary part of the polarizability tensor components and the changes of the absorption and scattering cross-sections with variations in the size, shape, and material of nanoparticles are analyzed. It is found that the position of the transverse surface plasmon resonance (SPR) in rod-like nanoparticles of the considered shapes is practically insensitive to the changes of their semiaxes, whereas the increase of the aspect ratio leads to a “blue” shift of the longitudinal SPR. It is shown that the use of the model of effective prolate spheroid provides satisfactory agreement with experimental data obtained at the longitudinal SPR frequencies and does not require the application of complicated computational methods.